Let’s Calculate Kids: The Development of 3D Augmented Reality Mobile Learning Apps to Enhance Learning Engagement in Basic Calculation for Preschools - Halim, Siti Noormashetah; Zamri, Masturina Balqiz; Muhamad Azli, Norfaraliyana; Mohamed Ali @ Md Hani, Mohd Hatta (Multidisciplinary Applied Research and Innovation, 2022)
Mathematics is an excellent way to develop mental discipline while also encouraging logical thinking and mental assertiveness. Furthermore, comprehending the content of other educational courses such as science, social studies, and even music and art relies heavily on mathematical knowledge. The COVID 19 epidemic is currently sweeping the whole world, including Malaysia, which makes learning Mathematics difficult. This article will look at how learning techniques may be improved to make them more engaging and relevant at this time of epidemic in mathematics courses, with a beneficial influence on students. All learning activities are now focused toward teaching and learning approaches from home in order to preserve educational continuity (PDPR). It is critical that new teaching and learning facilities be provided for mathematics. This review article will examine mobile learning techniques (Lets Calculate Kids) for the subject of mathematics. This research will also look at the elements that contribute to improved learning engagement. The target group was then put through many rounds of testing to validate it. The effectiveness of the Lets Calculate Kids app in early mathematics acquisition will probably definitely be expanded to the study of other topics in other industries.